Identification and Expression Analyses of Olfactory Gene Families in the Rice Grasshopper, Oxya chinensis, From Antennal Transcriptomes - Cui, Yang; Kang, Cong; Wu, Zhongzhen; Lin, Jintian (Frontiers in Physiology, 2019)
The rice grasshopper Oxya chinensis is an important agricultural pest of rice and other gramineous plants. Chemosensory genes are crucial factors in direct interactions with odorants in the olfactory process. Here we identified genes encoding 18 odorant binding proteins (OBPs), 13 chemosensory proteins (CSPs), 94 odorant receptors (ORs), 12 ionotropic receptors (IRs), and two sensory neuron membrane proteins (SNMPs) from O. chinensis using an transcriptomic approach. Semi-quantitative RT-PCR assays revealed that six OBP-encoding genes (OchiOBP4, 5, 8, 9, 10 and 14), one CSP gene (OchiOBP10) and two IR genes (OchiIR28 and 29) were exclusively expressed in antennae, suggesting their roles in olfaction. Real-time quantitative PCR analyses revealed that genes expressed exclusively or predominantly in antennae also displayed significant differences in expression levels between males and females. Among the differentially expressed genes, 17 OR-encoding genes, one CSP- and one SNMP-gene showed female-biased expression, suggesting that they may be involved in some female-specific behaviors such as seeking oviposition site; whereas the three remaining OR-encoding genes showed male-biased expression, indicating their possible roles in sensing female sex pheromones. Our results laid a solid foundation for future studies to reveal olfactory mechanisms as well as designing strategies for controlling this rice pest.